2021
DOI: 10.1080/20008198.2021.1984050
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status and risk factors during Covid-19 pandemic in the Croatia’s adult population

Abstract: Background : The Covid-19 pandemic is associated with adverse mental health outcomes for people worldwide. Objective : The study aimed to assess mental health during the Covid-19 pandemic and the key risk factors from the human ecology perspective in Croatia’s adult population. Method : An online panel survey with 1,201 adult participants (50.1% women) was done with a nationally representative sample in terms of gender, age, and country region four mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 42 publications
2
24
0
4
Order By: Relevance
“…Moreover, indicators such as life satisfaction and loneliness remained generally stable during the first year of the pandemic. Similar results were obtained on Croatia's general adult population (Ajduković et al, 2021) during a fairly relaxed period in July 2020. Depression, anxiety, stress, and adjustment disorder were lower than those reported in previous studies conducted earlier in the pandemic with a non-representative sample (Jokić Begić et al, 2020).…”
Section: Mental Health During Coronavirus Pandemicsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, indicators such as life satisfaction and loneliness remained generally stable during the first year of the pandemic. Similar results were obtained on Croatia's general adult population (Ajduković et al, 2021) during a fairly relaxed period in July 2020. Depression, anxiety, stress, and adjustment disorder were lower than those reported in previous studies conducted earlier in the pandemic with a non-representative sample (Jokić Begić et al, 2020).…”
Section: Mental Health During Coronavirus Pandemicsupporting
confidence: 84%
“…Our analyses have shown that sociodemographic features were indeed relevant for the most mental health and socio-psychological outcomes. Regarding mental health, it seems that women are more vulnerable than men; they obviously have experienced more emotional difficulties and pandemic-related stress than men, as corroborated by other studies in Croatia (Ajduković et al, 2021;Jokić-Begić et al, 2021) and elsewhere (e. g. Lotzin et al, 2021). Further, more stress was also experienced by young adults (18-29 years), and more stress and emotional difficulties among those who estimated their standard of living below the average, those less educated and unemployed (either being unemployed because of the coronavirus or for some other reason).…”
Section: Discussionsupporting
confidence: 70%
“…Quick transmission of the virus resulting from globalization and people’s mobility has caused global traumatic stress ( Heitzman, 2020 ). The sense of instability and uncertainty connected with the pandemic, the need to change our plans, potential job loss and financial insecurity combined with social isolation have generated the feeling of losing control of our lives ( Ajduković et al, 2021 ; Giorgi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of July 2020, a longitudinal study "Psychological adaptation and coping during the coronavirus pandemic" was launched by a team gathered around the Croatian Society for Traumatic Stress, which was conducted over 18 months at four time points (Ajduković et al, 2021b). In this online probability survey (N = 1,201) the sample included an equal share of men and women (50%), and their educational structure and regional affiliation were representative of Croatia.…”
Section: The First Croatian Studies On the Effects Of The Covid-19 Pa...mentioning
confidence: 99%
“…The first time point of the study showed that people with an earlier mental health diagnosis, people who assessed their health condition as at risk, people with below-average income and who followed the news for more than two hours a day were at higher risk. At the same time, psychological resilience was shown to be a protective factor (Ajduković et al, 2021a). Although younger people (18 to 25 years old) showed more psychological difficulties due to the COVID-19 pandemic, they also showed more flexibility in adapting to new conditions (Bakić, 2021).…”
Section: The First Croatian Studies On the Effects Of The Covid-19 Pa...mentioning
confidence: 99%